The Essential of Trembesi in Djawatan: Identifikasi Persebaran Pohon Trembesi sebagai Penentu Biodiversitas di Kawasan Hutan Djawatan - Rosyidah, Aminatur; Hidayah, Elok; Lindasari, Lindasari (Biocaster : Jurnal Kajian Biologi, 2024)
Trembesi (Samanea saman) plays an important role in the Djawatan forest area. The presence of Djawatan forest in the city adds vital value to trembesi, such as maintaining ecosystem stability, soil stability, water supply stability, O2 supply, and CO2 absorption. This study aims to determine the density of trembesi trees in the Djawatan forest area. The presence of trembesi in the Djawatan forest is crucial for the numerous flora and fauna sheltered beneath it. Therefore, understanding the distribution pattern of trembesi in the Djawatan forest area is essential to ascertain environmental influences on the growth of trembesi. The research method used in this study was descriptive qualitative through observation and interviews. Trembesi distribution in this study was observed in four different zones: waterfront, rice field edge, central Djawatan forest, and settlement edge. Based on the research results, it is known that trembesi distribution is influenced by the surrounding environmental conditions. This is evidenced by data showing that the highest average density of trembesi is found in the central Djawatan forest area, which is 0.50%.